Validating bowel preparation scales - Heron, Valérie; Parmar, Robin; Ménard, Charles; Martel, Myriam; Barkun, Alan N. (Endoscopy International Open, 2017)
Background and study aim Few scales assessing bowel preparation quality have been validated, and direct between-scale comparisons remain scarce. The aim of the study was to compare inter- and intra-rater reliability, predictive abilities for clinical outcomes, and ease of use for each scale.Methods Colonoscopy video recordings highlighting five colonic segments after washing were viewed independently by three physicians, and cleanliness was evaluated using the Boston Bowel Preparation Scale (BBPS), the Chicago Bowel Preparation Scale (CBPS), and the Harefield Cleansing Scale (HCS) in randomized order. Kappa or intraclass correlations quantified intra- and inter-rater reliability. Ease of use was evaluated (1 – 10 scale, 1 = easy), as were associations between scores, adenoma detection, and adequacy of preparation to exclude lesions ≥ 5 mm. Results Among 83 colonoscopy videos, indications included screening or surveillance in 72.3 %. Mean (± SD) scores of the respective three raters were 5.17 ± 1.57, 6.49 ± 1.48, and 5.12 ± 1.21 for BBPS, and 23.73 ± 6.01, 28.39 ± 5.47, and 24.75 ± 5.83 for CBPS, while successful HCS scores (grade A or B) were given for 76 %, 89 %, and 63 % of examinations. Intra-rater reliability ranges were 0.88 – 1.00, 0.83 – 1.00, and 0.62 – 1.00 for BBPS, CBPS, and HCS, respectively. Similarly, inter-rater reliability ranges were 0.50 – 0.79, 0.64 – 0.83, and 0.28 – 0.52, respectively. Sources of disagreement included varying rater strictness, which was possibly most marked for preparations rated as intermediate. Overall, associations between preparation scores and adenoma detection lacked statistical significance.Conclusion The BBPS and CBPS showed the best inter- and intra-rater reliability, and the BBPS was considered the easiest to use. Further studies are needed to determine an optimal adequacy threshold for these scales, with the goal of predicting clinical outcomes and determining the appropriate interval to the next colonoscopy.